LITERASI INFORMASI MAHASISWA TINGKAT AKHIR DALAM MENULIS SKRIPSI DI FISIP UPN â€œVETERANâ€ JAKARTA - Sevilla, Vinta; Azwar, Azwar (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2019)
This study aims to determine the information literacy of students through the use of e-journal in writing a thesis to complete the final assignment. The method used is a descriptive quantitative approach through a questionnaire conducted to 155 respondents. The sampling method uses purposive sampling. This study takes the concept of Big6 information literacy developed by Berkowitz and Eisenberg. The questions asked to use the variables of the Big6 results. The results of this study are that student information literacy in the use of e-journal to complete the thesis is classified as 'quite good' as the respondents are already used to using electronic and online based media, but in information retrieval is still low with effectively and efficiently. This is seen from each sub-variable that is submitted through the question items that are answered.